PENGELOLAAN OBJEK WISATA PANTAI TRIKORA 4 OLEH DINAS PARIWISATA KABUPATEN BINTAN TAHUN 2016 - Asma Juliano Woi; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One of beach tourist attractions in Bintan Regency is Trikora Beach, located in Malang Rapat Village, Gunung Kijang Sub-District, Bintan Regency. Trikora Beach has 4 sections which are Trikora 1, Trikora 2, Trikora 3, and Trikora 4. Trikora Beach 4 is one of beaches managed by The Government. Trikora Beach 4 was purchased in 2002 and was began preparations for constructing in 2004 managed by the Bintan Regency of Tourism Office. Trikora Beach 4 has the potential to be managed and developed. Trikora Beach 4 offers special attraction with calm waves and white sand. Due to the lack of funds which affects on the maintenance of facilities and infrastructure, causing Trikora Beach 4 is not optimally managed. The problem statement of this research is to find out why The Management of Trikora Beach 4 as A Tourist Attraction has not been optimally managed by Bintan Regency of Tourism Office, Riau Islands Province?This study aims to determine The Management of Trikora Beach 4 as A Tourist Attraction by Bintan Regency of Tourism Office 2016. This study used qualitative research with descriptive type of research. The information techniques used are interviews and documentation. Data analysis used is limited to data processing techniques or facts obtained by developing categories that are in accordance with the objectives of research and interpretation based on appropriate theories.The results showed that Trikora Beach 4 as tourist attraction is managed by Tourism Office and the employees are directly employed by Bintan Regency of Tourism Office. The Management of Trikora Beach 4 is not yet maximally managed, this could be seen from its planning, organizing, mobilizing, monitoring and evaluation.There are obstacles that make this area is not optimally managed, among others are the lack of funds that has an impact on the maintenance of facilities and infrastructure at the location of the tourist attraction, Technical Service Centre (UPT) is not yet established, non-optimal supervision by Bintan Regency of Tourism Office, and not having an Trikora Beach 4 Tourist Safety and Security Team.Keywords: Local Government, Management, Tourism